Expanding the Phenotype of the FAM149B1-Related Ciliopathy and Identification of Three Neurogenetic Disorders in a Single Family - Sandy Siegert (MDPI AG, 2021)
Biallelic truncating FAM149B1 variants result in cilia dysfunction and have been reported in four infants with Joubert syndrome and orofaciodigital syndrome type VI, respectively. We report here on three adult siblings, 18 to 40 years of age, homozygous for the known FAM149B1 c.354_357delinsCACTC (p.Gln118Hisfs*20) variant. Detailed clinical examinations were performed including ocular and gait analyses, skeletal- and neuroimaging. All three patients presented with neurological and oculomotor symptoms since birth and mild skeletal dysplasia in infancy resulting in characteristic gait abnormalities. We document mild skeletal dysplasia, abnormal gait with increased hip rotation and increased external foot rotation, ataxia, variable polydactyly, ocular Duane syndrome, progressive ophthalmoplegia, nystagmus, situs inversus of the retinal vessels, olfactory bulb aplasia, and corpus callosal dysgenesis as novel features in FAM149B1-ciliopathy. We show that intellectual disability is mild to moderate and retinal, renal and liver function is normal in these affected adults. Our study thus expands the FAM149B1-related Joubert syndrome to a mainly neurological and skeletal ciliopathy phenotype with predominant oculomotor dysfunction but otherwise stable outcome in adults. Diagnosis of FAM149B1-related disorder was impeded by segregation of multiple neurogenetic disorders in the same family, highlighting the importance of extended clinical and genetic studies in families with complex phenotypes.